Synthesis and Antihypoxic Activity of 2-aryl-7,7-dimethyl-5-oxo-5,6,7,8-tetrahydroquinoline-4-carboxylic Acids and Their Reaction Products with Substituted Hydrazines - K. V. Namyatova; S. S. Zykova; D. S. Ovchinnikov; S. N. Shurov (Разработка и регистрация лекарственных средств, 2023)
Introduction. Hypoxia is a violation of oxidative processes in tissues that occur when oxygen is insufficiently supplied to them or when its utilization is disrupted during biological oxidation. Chronic hypoxic damage plays an important role in the occurrence and development of various diseases, which necessitates the synthesis of new compounds with antihypoxic activity.Aim. The purpose of this study is to synthesize and investigate the antihypoxic activity of 2-aryl-7,7-dimethyl-5-oxo-5,6,7,8-tetrahydroquinoline-4-carboxylic acids and their reaction products with substituted hydrazines.Materials and methods. 2-Aryl-7,7-dimethyl-5-oxo-5,6,7,8-tetrahydroquinoline-4-carboxylic acids (I–VI) were obtained with high yields as a result of the interaction of 4-aroyl-2,4-dioxobutane acids with 3-amino-5,5-dimethylcyclohex-2-enone. Interaction of 2-aryl-7,7-dimethyl-5-oxo-5,6,7,8-tetrahydroquinoline-4-carboxylic acids with benzyl- and (2-phenylethyl)hydrazines 5-aryl-2-benzyl- and 2-(2-phenylethyl)-8,8-dimethyl-3,7,8,9-tetrahydro-2H-pyrido[4,3,2-de]cinnoline-3-ones (VII–XII) were obtained. As a result, 12 compounds were synthesized. The study of the antihypoxic activity of the obtained compounds was carried out in vivo on a model of normobaric hypoxia with hypercapnia.Results and discussion. The synthesized compounds were tested for the presence of antihypoxic action. The most pronounced antihypoxic activity is characteristic of compounds VI and VIII, which have a methoxy group and a methyl radical in the para-position of the phenyl substituent at C5, respectively. The presence of chlorine in the structure of compound III, fluorine in compound X and the absence of substituents (compounds I and VII) contribute to the prohypoxic effect. According to the results of the study, both quinolincarboxylic acids and pyridocinnolines are potential antihypoxants.Conclusion. A comparative analysis of the antihypoxic activity of the synthesized compounds was carried out, the relationship between their structure and severity of action was established, the most active substances were identified.